Persistence of Mucuna pruriens biomass during the dry season along an agroecological transect in Benin - Carsky, R.J.; Eteka, A. (2000)
The persistence of Mucuna biomass was observed in three sites in the Benin Republic during the dry season of 1997-98. At Parakou, in the southern Guinea savanna agroecological zone of northern Benin, Mucuna dry matter (DM) decreased at a rate of approximately 0.2t/ha/month. At the onset of the next rainy season, an early Mucuna (Mucuna pruriens var. utilis Rajada) cultivar had less than 2t DM/ha and late varities (Mucuna pruriens var. utilis, preta, and cochinchinensis) had more than 4 t/ha. In southern Benin, Mucuna dry matter increased significant at Hayakpa, a nondegraded site on the Allada Plateau, and remained constant at Adingnigon, a highly degraded site on the Abomey Plateau. At the onset of the subsequent rainy season, Mucuna dry matter averaged 6.0 t/ha at Hayakpa and 4.7 t/ha at Adingnigon. Prediction of growth and persistence of Mucuna must take into account duration of the variety, the soil characteristics, the agroecological zone, planting date, and crop associations during the establishment phase. The Mucuna fallow system should be primarily for weed suppression where its biomass is likely to persist.